The association between wasting nutritional status and delayed of child development in children age 12 – 60 months in Wangaya General Hospital, Denpasar, Bali - Michelle Husin; Gede Wikananda; I Wayan Bikin Suryawan (DiscoverSys Inc., 2019)
Background: Sub-optimal nutritional status in Indonesia is still a continuing problem. There is no significant change in the prevalence of sub-optimal nutritional status. First 1000 days of life is a golden period of brain development. Failure of providing adequate nutrition can lead to the deviation of child development.Objective: To investigate the association between wasting nutritional status and delayed child developmentMethods: A cross sectional study was conducted in this study. Fifty eligible subjects were taken from April 2018 to July 2018 using consecutive sampling methods. Characteristics such as child age, sex, exclusive breastfeeding status, birth weight, birth height, current weight, current height, nutritional status, prematurity, and mother’s working status recorded. Child nutritional status was recorded and assessed with the WHO growth chart. Child developmental status was measured with the pre-screening development questionnaire (KPSP). Score ≤ 8 was assumed as a deviation in child developmental status.Results: Wasting nutritional status is significantly associated with child development (p=0.041, CI -0.013-0.096). Prevalence ratio is 3.5 shows that wasting nutritional status is a risk factor for delayed child development. Domain for child developmental delay was 54,5% has language & speech delay, 36,4% has a gross motor delay, and 9,1% has social & independency delay.Conclusion: There is an association between wasting nutritional status and delayed child development. The most often child developmental delay found is speech delay.